The mortality impact of cholera in Germany - Kalle Kappner (European Historical Economics Society (EHES), 2025)
This paper presents the first comprehensive quantitative account of epidemic cholera in 19th-century Germany. Using a new dataset based on archival sources, it documents nearly half a million cholera deaths, along with outbreak timing and population at risk, across 2,685 cities and 852 rural counties within the 1871 German Empire. I document five stylized facts: First, cholera was primarily an urban disease, with city death rates averaging 3.5 times higher than in rural areas. Second, mid-sized cities (1,000-3,000 inhabitants) were the most severely affected. Third, cholera's geographic epicenter focused on the less developed North-East territories (Central Poland), but shifted South-West over time. Fourth, outbreaks spread more rapidly across regions and within cities over time, despite declining overall mortality. Fifth, local epidemics converged in severity across locations but became more spatially clustered over time. Understanding these complex patterns requires analysis of cholera's interaction with dominant trends of 19th-century Western development, including public health reforms, urbanization, market integration, and political change. While the rich cholera historiography has long recognized these links, it merits greater attention from quantitative social scientists, including economic historians. Datasets like this one are the foundation for that engagement.
Keywords: J11; N33; 330; Historical Epidemiology; Demography; Mortality Transition